"Click" polymerization: A convenient strategy to prepare designer fullerene materials. (15th October 2016) - Krishnamurthy, Munusamy; Krishnamoorthy, Kothandam; Arulkashmir, Arulraj; Raghavendra, V.; Murali, Adhigan; Jaisankar, Sellamuthu N.; Murugan, P.; Gurusamy-Thangavelu, Senthil A.; Nasar, A. Sultan; Mandal, Asit Baran; Samanta, Debasis
Abstract: "Click" polymeric assemblies of fullerenes, thiophenes and aryl compounds were prepared for the first time to study their spectroscopic/chemical/electronic characteristics and possible applications in photovoltaic cells. The GPC and NMR spectroscopic data confirmed a moderate to high degree of polymerization while microscopic pictures showed well-defined arrangements of fullerenes. The FTIR studies indicated that the product is free from starting azide materials, whereas thermogravimetric analysis data suggested a good stability. Band gap of the material was determined using UV–Vis spectroscopy, cyclic voltammetric techniques and compared with computational investigation. The fullerene copolymer was fabricated as acceptor material in a bulk heterojunction photovoltaic cell. Graphical abstract: Highlights: "Click" copolymerization was successfully performed on functionalized fullerenes. The strategy allows linking of multiple aromatic rings with fullerenes. The material was successfully used as a component in solar cell device fabrication.